Collophora hispanica, a New Pathogen and Potential Threat to the Almond Industry in Iran. Issue 10 (27th June 2016) - Arzanlou, Mahdi; Ghasemi, Saeid; Baradaran Bagheri, Maryam
Abstract: Trunk diseases are potential threats for almond productivity and longevity worldwide, including Iran. In a recent survey on fungal species associated with trunk diseases of almonds in north‐western Iran, Collophora isolates (tentatively identified as Collophora hispanica ) were recovered with high frequency from wood samples with internal necrosis and brown to black vascular streaking of almond trees showing symptoms of decline. However, the pathogenic potential of Collophora isolates on almond trees in Iran remains unproven. In this study, the identity of the isolates was further confirmed as C. hispanica based on a combination of morphological data and sequence data of ITS‐rDNA region, and pathogenicity of C. hispanica isolates on almond was evaluated using excised shoot method and in greenhouse experiments . Collophora hispanica isolates induced lesions statistically different from the control, in both excised shoot method and greenhouse assays. Significant differences were observed among the isolates in the length of the lesion induced on wood. Collophora hispanica should be considered as the main trunk pathogens of almond trees in north‐western region of Iran. The distribution and host range of this new pathogen on almond remains to be studied.